Pre-Selection test to identify high responder donor goats - Cueto, Marcela Isabel; Gibbons, Alejandro Eduardo; Balaro, Mario Felipe Alvarez; Brandao, Felipe Zandonadi; Maia, A.L.R.S.; Souza-Fabjan, Joanna Maria Gonçalves; Fonseca, Jeferson Ferreira (2017)
The aim of the study was to evaluate the feasibility of pre-selection of high or low responder does prior to the superovulatory protocols. Twenty Saanen does received 800 IU of equine chorionic gonadotropin (eCG) at the end of long-term progestogen treatment. Fourteen days later, a second progestogen protocol associated with a multiple-dose follicle stimulation hormone (FSH) treatment (5 IU/kg of FSH, in six decreasing doses between days 4 to 6 of the protocol) was administered. Transrectal ultrasound was used to assess the follicular status at the beginning of superovulatory treatments, at the oestrous onset and on the seventh day of the oestrous cycle for counting corpora lutea (CL). A significant lower number of CL was obtained in eCG-treated in comparision with FSH-treated does (p < 0.05). A quartic regression was able to explain the relationship between the number of CL in response to both treatments (r2=0.50; p < 0.05). Seventy per cent (14 of 20) of does maintained the same ovulatory response (high or low) after treatments. The Kappa (κ = 0.40; p < 0.05) and Spearman (rs = 0.39; p = 0.08) coefficients were able to show a relationship between treatments. Regarding the follicular status, there is a significant relationship between the number of small follicles (r = 0.71; r2=0.47; p < 0.01) and total follicles (r = 0.60; p < 0.01) at eCG and first FSH dose with the number of CL. Moreover, it was found a negative relationship between the presence of large follicles and the number of CL in response to eCG treatment (r = −0.44; p < 0.05), but not from FSH (p > 0.05). In conclusion, the screening test with eCG has the potential to identify Saanen does that will better respond to the superovulatory protocol with FSH. In addition, it highlighted the importance of an ultrasound evaluation prior to the beginning of superovulatory treatments with FSH to characterize the follicular status and identify the potential donors of high ovulatory response in MOET programmes in goats.